High sodium intake increases interstitial lung disease and pulmonary sarcoidosis based on the Global Burden of Disease study 1999–2019 - Hu, Zhigang; Tian, Yufeng; Yang, Ailan; Song, Xinyu (Scientific reports, 2024)
This study investigated the relationships between dietary sodium intake and the incidence and prevalence of interstitial lung disease (ILD) and pulmonary sarcoidosis using data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2019. This study assessed the strength of the abovementioned relationships via LASSO analysis and a generalized additive model with Poisson regression and determined the nonlinear and lagged effects via a distributed lag nonlinear model (DLNM). In the past three decades, global dietary sodium intake has decreased gradually. Two LASSO and generalized additive analyses both suggested that dietary sodium intake is obviously correlated with the incidence and prevalence of ILD and pulmonary sarcoidosis. The overall exposure‒response curve revealed a dose‒effect relationship between dietary sodium intake and the incidence and prevalence of ILD and pulmonary sarcoidosis. The maximum lag-specific RR of extremely high dietary sodium intake was 1.75 (95% CI: 1.61–1.91, lag 0 year) for incidence and 3.19 (95% CI: 2.24–4.53, lag 0 year) for prevalence relative to the reference. Our study suggests that dietary sodium intake is positively associated with the incidence and prevalence of ILD and pulmonary sarcoidosis. These findings may have important policy implications for dietary sodium intake-reduction strategies to decrease the burden of respiratory diseases and promote public health.